Strategies of identity formation : Youth of Turkish Ddscent in Germany - Mehdi, Ali (VS College, 2012)
Integration of immigrants and their descendants has been a socially sensitive and a politically pressing issue in Germany, particularly in recent decades. Being the largest immigrant group in the country, and for a number of other reasons, the spotlight has been on people of Turkish descent. From a sociological perspective, the process of identity formation is a critical step in the direction of integration. If immigrants of Turkish descent are to be integrated in the society, it is crucial to inquire how they conceive of themselves, and perceive how they are conceived by the so-called locals. Heeding Goethe, Ali Mehdi goes out into broad and open land to conduct in-depth interviews with seven young men of Turkish descent, born in Germany, and to analyze - utilizing the empathetic approach of the German hermeneutic tradition - the rich diversity of identity strategies that the interviewees employ.